EKSPERIMENTASI MODEL PEMBELAJARAN SAVI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI GAYA BELAJAR - Elsi Indriasari (Mat-Edukasia, 2019)
This study aims to describe mathematical communication skills taught with the Somatic Auditori Visual and Intellectual (SAVI) learning model better than conventional learning as a whole and based on auditory, visual, and intellectual learning styles. This study uses a quantitative approach and an experimental method with a 2 × 3 factorial design. Determination of samples using simple random sampling technique. Data collection techniques were carried out with test instruments in the form of description questions and mathematics learning style questionnaires. Data analysis techniques used are different tests (t-test) and two-way ANOVA. The results showed that: (1) mathematical communication skills taught with SAVI learning models were better than conventional learning, (2) students' mathematical communication skills with auditory, visual, and intellectually learning styles taught with SAVI learning models were better than conventional learning , and (3) there is an interaction between the SAVI learning model and conventional learning in terms of learning styles in influencing mathematical communication skills. Keywords: SAVI, mathematical communication skills, learning styles